RANCANG BANGUN ALAT MONITORING KUALITAS UDARA BERBASIS NODEMCU ESP8266 (HARDWARE) - Raywanda Affandi Harahap; Mohammad Yanuar Hariyawan (Politeknik Caltex Riau, 2021)
Abstract In 2015, forests in the Riau region experienced severe fires that also resulted in haze. The impact of the disaster, especially the Caltex Riau Polytechnic, was disrupted teaching and learning activities. The application of technology in the form of sensors as a system monitoring air quality can be used to assist in making emergency decisions for haze disasters, especially the Caltex Riau Polytechnic environment. The implementation of the GP2Y1010AU0F sensor as a detector for PM10 air levels, the DHT11 sensor as a temperature and humidity detector, the MQ-7 sensor as a detector for carbon monoxide levels in the air and the use of the ESP8266module WiFi as a medium for sending sensor data to the web as a monitoring system for sensors to users. PM10 sensor testing has an average error rate of 8.2% with a comparison tool, a temperature sensor of 8.42% and a humidity sensor of 2.89%. Monitoring is carried out via the internet via the web so that remote monitoring can be carried out as long as it is connected to the internet network. With this system, air quality information can be found through the website in real time. Keywords: haze, monitoring, decision making, realtime